HIV/AIDS-related stigma and access to HIV treatments by people living with HIV/AIDS: A case study of selected states in North-West Nigeria (2011)
Objectives: To study the prevalence of HIV-related stigma and the effect of stigma on HIV treatment adoption among PLWHA attending HIV treatment locations in some selected states in the North-West geopolitical zone of Nigeria. Methods: A cross-sectional survey was conducted (using structured questionnaires) among PLWHA in three selected states in the North-West geopolitical zone of Nigeria and Abuja, the Federal Capital Territory (FCT). The multiple logistic regressions analysis was used to determine factors associated with HIV-related stigma and adoption of HIV treatment. Results: It was found that 71(21.3%), 88(26.3%) and 43(12.8%) of the participants were facing HIV-related stigma from their place of works, the public and their family members. Also, the results of the logistic regressions show that PLWHA who have no formal education and those with primary education were less likely to face stigma from the public (OR-0.212; 95% CI-0.064–0.702; p < 0.05) and their employers (OR-0.236; 95% CI-0.072–0.775; p < 0.05) respectively. Conclusion: Although majority of the participants claimed not to be facing any form of HIV-related stigma, the prevalence of HIV-related stigma observed (job related stigma – 21.3%, stigma from the public – 26.3% and stigma from family members-12.8%) among the participants in this study still calls for concern.